PIWI pathway: bridging acute myeloid leukemia stemness and cellular differentiation - Garcia-Silva, M. R.; Márquez, M. E.; Pinello, N. (Frontiers in Cell and Developmental Biology, 2024)
PIWI proteins are stem cell-associated RNA-binding proteins crucial for survival of germ stem cells. In cancer, PIWI proteins are overexpressed. Specifically, PIWIL4 is highly expressed in multiple cancers with the highest levels found in acute myeloid leukemia (AML), an aggressive malignancy propagated by a population of leukemia stem cells (LSCs). Bamezai et al. (Blood Journal, blood, 2023, 142, 90–105) demonstrated that PIWIL4 supports AML blasts and LSCs but is not necessary for healthy human hematopoietic progenitor stem cells (HSPCs) function in vivo. PIWIL4 in AML acts by preventing the accumulation of R-loops in key genes for LSCs persistence implicated in: DNA damage, replicative stress, and transcription arrest. We report that PIWIL4 expression significantly decreases in THP-1 monocytes exposed to a differentiating agent, suggesting a potential role for PIWIL4 in maintaining the undifferentiated state of myeloid cells. PIWIL4 overexpression could lead to the emergence of LSCs, driving leukemia propagation and maintenance. Our findings correlate with the persistent overexpression of PIWIL4 in myeloid cancers as reported by Bamezai et al., and suggest that PIWIL4 may be involved in myeloid cell differentiation. In this perspective, we highlight recent findings on the implication of PIWI pathway in maintaining AML stemness. Additionally, we propose further investigation on the role of PIWI pathway in oncogenesis and cellular differentiation as a strategy to identify biomarkers and therapeutic targets for AML.